2018
DOI: 10.3390/app8010075
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Strength Monitoring for Concrete Structures Using EMI Technique Incorporating with Fuzzy Logic

Abstract: This study estimates the strength of a special mixture of high-strength concrete (HSC) with admixtures for use in a nuclear power plant (NPP). Nuclear power plant structures need a HSC with some additional qualities to operate the safe options. For this purpose, the experimented concrete was specially designed to fulfill the required qualities of NPP. For gaining these desirable qualities, it needs to monitor the concrete strength development process. Here, the PZT materials were used as sensors to acquire dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…The influence of setting and initial hardening of concrete were investigated to detect the gradual bonding between a steel reinforcing bar and fresh concrete [ 29 ]. With the help of fuzzy logic [ 30 ], the strength development process of a high-strength concrete was monitored. An artificial neural network algorithm to estimate the early-age strength of concrete based on the EMI dynamic response of PZT sensor was proposed [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of setting and initial hardening of concrete were investigated to detect the gradual bonding between a steel reinforcing bar and fresh concrete [ 29 ]. With the help of fuzzy logic [ 30 ], the strength development process of a high-strength concrete was monitored. An artificial neural network algorithm to estimate the early-age strength of concrete based on the EMI dynamic response of PZT sensor was proposed [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, both the numerical and experimental studies validate that the multi-sensing EMI method can be used to monitor the grouting compactness. EMI methods have been widely used for concrete hydration monitoring [74][75][76][77], and future work will involve explore concrete hydration monitoring using the proposed multi-sensing EMI.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude by stating that the approach proposed in the work has the potential to be applied to in situ hydration monitoring of reinforced concrete structures. More research in the field of concrete strength prediction can be found in recent studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Investigations On the Emi Techniquementioning
confidence: 99%